Politics of the Event : Time, Movement, Becoming. - Lundborg, Tom (Interventions., 2011)
Despite occupying a central role and frequently being used in the study of international politics, the concept of the "event" remains in many ways unchallenged and unexplored. By combining the philosophy of Gilles Deleuze and his concept of the event with the example of 9/11 as an historical event, this book problematises the role and meaning of "events" in international politics. Lundborg seeks to demonstrate how the historical event can be analysed as a practice of inscribing temporal borders and distinctions. Specifically he shows how this practice relies upon an ongoing.